Integration of light and temperature signaling pathways in plants. Issue 2 (26th February 2022) - Qi, Lijuan; Shi, Yiting; Terzaghi, William; Yang, Shuhua; Li, Jigang
Abstract: As two of the most important environmental factors, light and temperature regulate almost all aspects of plant growth and development. Under natural conditions, light is accompanied by warm temperatures and darkness by cooler temperatures, suggesting that light and temperature are tightly associated signals for plants. Indeed, accumulating evidence shows that plants have evolved a wide range of mechanisms to simultaneously perceive and respond to dynamic changes in light and temperature. Notably, the photoreceptor phytochrome B (phyB) was recently shown to function as a thermosensor, thus reinforcing the notion that light and temperature signaling pathways are tightly associated in plants. In this review, we summarize and discuss the current understanding of the molecular mechanisms integrating light and temperature signaling pathways in plants, with the emphasis on recent progress in temperature sensing, light control of plant freezing tolerance, and thermomorphogenesis. We also discuss the questions that are crucial for a further understanding of the interactions between light and temperature signaling pathways in plants. Abstract : Light and temperature are tightly‐associated signals for plants, and plants have evolved a wide range of mechanisms to simultaneously perceive and respond to dynamic changes in light and temperature. This review summarizes the current understanding of the molecular mechanisms integrating light and temperature signaling pathways in plants.